132 Impact of Experimentally Shortened Sleep on Meal Timing in Adolescents. (3rd May 2021) - Duraccio, Kara; Whitacre, Catharine; Beebe, Dean
Abstract: Introduction: Short sleep increases the risk for obesity in adolescents. One potential mechanism relates to when eating occurs, rather than what or how much is eaten. This study investigated the impact of shortened sleep on meal timing and late evening eating in adolescents. Methods: 93 healthy 14- to17-year-olds (62% female) completed a within-subject counterbalanced experimental sleep manipulation, engaging in shortened sleep (SS; 6.5 hours/night in bed) or healthy sleep (HS; 9.5 hours/night in bed), each for five nights, with order randomized. Sleep timing was verified through wrist-worn actigraphy. During each sleep period, adolescents completed 2-3 dietary recalls. Repeated-measure T-tests assessed the sleep manipulation effect on averaged times of the first and last eating episode, number of eating episodes after 8:00pm, and range of the daily eating period. Results: Youth averaged 2.2 hours/night longer sleep during HS than SS (p<.001). The timing of the first eating episode was similar across conditions, relative to the clock (SS=08:51, HS=08:52) and to time since waking (SS=1.8hr, HS=1.9hr). The timing of the last eating episode averaged later on the clock during SS (20:34) than HS (19:38; p<.001), resulting in a longer eating period (SS=11.7hr, HS=10.8hr, p<.001). Youth averaged more eating episodes after 8:00pm during SS (0.87) than HS (0.59, p<.001). The gap between last eating episode and sleep onset was larger in SS (4.1hr) than HS (2.8hr; p<.001). Notably, on average, adolescents last eating episodes during SS (20:34) were earlier than sleep onset in either condition, and were even 2 hours earlier than when they fell asleep during HS (M=22:30). In exploratory analyses, these effects did not systematically vary by experimental order of the sleep conditions, family income, or participant age, sex, or norm-referenced body mass index. Conclusion: Shortened sleep resulted in adolescents eating later and lengthening the daily period of time in which they ate, despite typically stopping eating well before sleep onset during healthy sleep. Late evening eating and long daily eating periods have been strongly associated with weight gain, which may help explain the link between shortened sleep and increased obesity risk in adolescents. Support (if any): R01HL120879